The location method of blade vibration events based on the tip-timing signal. (17th May 2021) - Liu, Zhibo; Duan, Fajie; Niu, Guangyue; Jiang, Jiajia; Zhi, Fengyao; Cheng, Zhonghai; Feng, Junnan; Xiong, Bing
Abstract: Tip-timing technology has been widely used to monitor blade vibration of the aeroengine. In the off-line analysis of tip-timing signals, it is key and a prerequisite in blade fault diagnosis to locate the vibration event accurately. It is the most common method used to locate abnormal vibration based on the correlation of tip-timing data in adjacent revolutions. However, the data in the adjacent revolutions only include little vibration information, which results in the location performance being susceptible to noise. This paper located the vibration event using the area of the ellipse calculated based on the two-parameter plot. The relationship between the area of the fitted ellipse and the blade vibration parameters was derived for the first time in this paper. The feasibility of the method was verified using the tip-timing data of the low-pressure fan of an aeroengine. The results showed that the method can locate both synchronous resonance and rotating stall accurately. Its performance in anti-noise interference was far superior to the correlation coefficient methods due to enough information provided by multi-revolutions rather than only two revolutions. The work in this paper is of great significance for the realization of automatic processing of tip-timing signals.